Feminis Santri: Tokoh, Pemikiran, dan Gerakan Feminis Berlatar Belakang Pesantren di Daerah Tapal Kuda Tahun 1990–2012: Female Islamic Boarding School Activists: Figures, Thoughts, and Feminist Movements with Pesantren Background in the Tapal Kuda Region, 1990–2012 - Harisudin Harisudin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
A feminist is a person or group of people focused on a social movement that fights against gender injustice in all aspects of life. Feminists also exist among religious individuals, including in Islam, where in this context, they are called Islamic student feminists. In the Tapal Kuda region, there are many feminists, both male and female, among Islamic students. This research takes five feminists as its subjects. These Islamic student feminists come from the administrators and teachers of pesantren. The issues addressed in their perspectives include polygamy, female leadership, domestic violence, and migrant labor. Feminis adalah seseorang atau sekelompok orang yang fokus pada gerakan sosial untuk melawan ketidakadilan gender dalam segala aspek kehidupan. Feminis juga hadir di kalangan religius, termasuk Islam, yang dalam konteks ini disebut feminis santri. Di daerah Tapal Kuda, terdapat banyak feminis, baik laki-laki maupun perempuan, di kalangan santri. Penelitian ini mengambil lima feminis sebagai subjek. Feminis santri tersebut berasal dari kalangan pengurus dan pengajar pesantren. Isu-isu yang dibahas dalam perspektif mereka meliputi poligami, kepemimpinan perempuan, kekerasan dalam rumah tangga, dan buruh migran.